Model Fenomena Imbibisi Kontra-Arus pada Media Berpori Homogen dalam Arah Horizontal - Vhinasy Andari; Muhammad Subhan; Riry Sriningsih (Journal of Mathematics UNP, 2019)
Abstract –The imbibition phenomenon is spontaneous flow of injected liquid (water) to the medium, causing displacement of native liquid (oil) to production wells. This phenomenon occurs in homogeneous porous medium. If oil is still in the medium then oil production is not yet optimally.To observe and analyze the phenomenon we usemathematical model. This model of imbibition phenomenon in form of nonlinear partial differential equations and the solution can be determined. The analysis representsoil that can be produced optimally if the saturation of water is increasing with respect to period as well as with respect to distance. Keywords – Mathematical Model, Imbibition Phenomenon, Homogeneous Porous Medium, Partial      Differential Equations